2009
DOI: 10.1021/jp902553n
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO on Supported Gold Nanoparticle Catalysts: A Comparative Study

Abstract: The adsorption of CO on three different gold nanoparticle catalysts supported on high surface area TiO 2 was studied using infrared transmission spectroscopy at room temperature and CO pressures typically used in CO oxidation reactions. The three, real-world catalysts were Au catalysts synthesized in our laboratory from thiol monolayer protected clusters (MPCs) and two commercial catalysts from the World Gold Council (WGC and AuTEK). Within experimental reproducibility, the adsorption data for the three cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 44 publications
5
55
2
Order By: Relevance
“…44,62,63 K R should be strictly interpreted in terms the total reactivity of adsorbed O 2 ; this can only correspond to a maximum value for the O 2 binding constant (K R is inversely related to the equilibrium binding constant). The Ni-Au data show dramatic increases in K R relative to pure Au.…”
Section: Resultsmentioning
confidence: 99%
“…44,62,63 K R should be strictly interpreted in terms the total reactivity of adsorbed O 2 ; this can only correspond to a maximum value for the O 2 binding constant (K R is inversely related to the equilibrium binding constant). The Ni-Au data show dramatic increases in K R relative to pure Au.…”
Section: Resultsmentioning
confidence: 99%
“…CO-adsorption infrared experiments were performed as described previously 49 . Approximately 25 mg of the sample were pressed into a 30 × 30 mesh Ti wire cloth (Unique Wire Weaving Co.) and mounted into a custom-built copper cell and vacuum chamber with a gas-phase optical-path length of 1.2 cm.…”
Section: Methodsmentioning
confidence: 99%
“…CO adsorption experiments were performed as previously described [50,51]. Briefly, approximately 25 mg of a pretreated sample was pressed into a 30 Â 30 Ti mesh (Unique Wire Weaving Co.).…”
Section: Co Heat Of Adsorption Measurements Via Ir Spectroscopymentioning
confidence: 99%
“…The entire gashandling system was rinsed with CO three times before exposing the sample. After collecting a background spectrum, the sample was exposed to a low pressure of CO and the surface was allowed to equilibrate for 5-10 min; previous work has shown that this is ample time for CO equilibration on Au catalysts [48,50,51]. An infrared spectrum was recorded and the pressure in the cell was slowly increased to the next pressure.…”
Section: Co Heat Of Adsorption Measurements Via Ir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation